Calcium and microbial diversity jointly regulate organic carbon stabilization in evaporative lakes - Guangquan Yu; Yang Li; Shengping Jin; Haochao Zhangsun; Xinyu Cai; Xuan Qiu; Deng Liu; Hongmei Wang (CATENA, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Freeze-drying-free camel-inspired cellulose-based aerogel foam for adaptive building thermal management - Tao Hai; Yu Yang; Qian Zhao; Yuqi Li; Xuejie Yue; Tao Zhang; Dongya Yang; Fengxian Qiu (Chemical Engineering Journal, 2026)

From agronomic performance to behavioral adoption of biochar‑based slow‑release fertilizer in saline‑alkali rice: A single‑season field trial and survey‑based SEM analysis - Zhixia Wang; Chang Dong; Junqiang Dong; Yang Cheng; Yuan Hu; Dan Liu; Yan Zhang; Zhen Qiu; Yanjiang Cai; Yongfu Li; Cheng Fu; Bing Yu (Journal of Environmental Chemical Engineering, 2026)

A dynamic adaptive electric field regulation strategy for stabilizing zinc anodes based on σ-electron donation - Hongxiang Zhao; Hua Yang; Jiayu Li; Yanwei Fu; Yu Zhao; Yuanshuai Wan; Yue Li; Yuliang Pang; Xingfa Qiu; Wenwen Duan; Weize Wang; Jiali Zhang; et al. (Chemical Engineering Journal, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Hierarchical in situ biomineralization-enhanced electroactive biofilm for high-efficiency antibiotic degradation - Zichen Li; Qi Qiu; Yan Feng; Shuming Yang; Yanzhen Yu (Bioresource Technology, 2026)

Three new ent -kaurene diterpenoid glucosides from the flowers of Inula japonica Thunb. - Zheng Niu; Jia-Qi Chen; Guan-Ke Liu; Li-Qin Ding; Chun-Yan Chen; Bing-Yang Zhang; Yu-Hong Li; De-Qin Zhang; Tie Yao; Feng Qiu (Natural Product Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The TORC-SnRK Axis: An Integrative Signaling Framework Balancing Growth and Stress Responses in Plants - Gao-Jia Yan; Qiu-Yan Yang; Yu-Song Liu; Jian Li; Hui Xue; Sheng Luan; Kun-Lun Li (Molecular Plant, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Cerrena unicolor laccases as sustainable biocatalysts for detoxifying hazardous long-chain phthalates and deconstructing plastic mulch films - Long-Bin Zhang; Jun Kang; Xiu-Gen Qiu; Zhou Cui; Yu-Tian Li; Yan Zheng; Yu Li; Yi Guan; Juan-Juan Yang; Chun Meng (Journal of Environmental Management, 2026)

Predictive Model on Limit Extension of Horizontal Well Drilling with Riserless Mud Recovery for Gas Hydrates in Offshore Areas - Jing Li; Bin Li; Bo Ning; Lujun Wang; Kaixiang Shen; Dongyu Yang; Xiaopeng Yan; Dezhi Qiu; Bin Zhu; Yanjiang Yu; Pengxiang Shen (Journal of Marine Science and Engineering, 2026)
Natural gas hydrate is an important emerging strategic resource, but low permeability makes the horizontal well length a key factor limiting productivity. A prediction model for friction torque of deepwater riserless drilling strings was established, and the segmented friction coefficient of hydrate horizontal wells was inverted and applied to the Shenhu hydrate reservoir. The results show that the main limiting factor for the extreme extension length of natural gas hydrate horizontal wells is the mechanical extreme extension length. The main affecting factor of the mechanical extreme extension length is the running limit of the screen pipe. The friction coefficient is the most significant factor affecting the mechanical extreme extension of horizontal wells, with the friction coefficient inside the casing in the high-build-rate section being the largest. The research identifies the primary factors governing the limit extension during horizontal well construction. The findings provide theoretical guidance for reservoir selection, well site determination, and wellbore configuration optimization in hydrate development. Ultimately, this contributes to maximizing single-well productivity and advancing the commercialization of hydrate resources.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Promote or inhibit? The impact of national park establishment on regional economic development: Evidence from Wuyishan National Park, China - Suwan Li; Honghong Yu; Mengyuan Qiu; Jiameng Yang (Journal for Nature Conservation, 2026)

GAN-FixMatch: A generative–semi-supervised deep learning framework for small-sample quantitative analysis in near-infrared spectroscopy of agricultural and pharmaceutical materials - Peng Li; Chenglong Qiu; Jinlong Duan; Yao Qin; Mingxing Li; Dandan Zhai; Xile Cheng; Yu Yang (Analytica Chimica Acta, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Enhancement of neutralization potency and breadth by an HIV nanoparticle vaccine containing TLR7/8 agonist 1 - Xiaoqian Xin; Yao Chen; Haoyue Li; Yunhan Zhang; Mengxue Li; Wei Zhou; Yanfeng Yang; Wei Cao; Jiaping Yu; Wenrong Yao; Yong Liu; Jianxiang Qiu; et al. (Chemical Engineering Journal, 2026)

Seneciphylline induces hepatotoxicity through mitochondrial apoptosis: mechanistic elucidation and in vitro-to-in vivo prediction via physiologically based pharmacokinetic modeling-facilitated reverse dosimetry - Yu-Shun Lu; Jiang Ma; Yuan Geng; Bing-Yan Zhang; Zheng Ding; Xiao-Li Shi; Yan-Yang Xu; Jing Qiu; Yong-Zhong Qian; Wen-Biao Shi; Lu Chen (Chemico-Biological Interactions, 2026)

Protodolomite formation in saline lakes: A machine learning perspective - Haochao Zhangsun; Yang Li; Shengping Jin; Xinyu Cai; Guangquan Yu; Xuan Qiu; Deng Liu; Hongmei Wang (Applied Geochemistry, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

The application and challenges of physical technology in modern agricultural plant protection - Shaobo Li; Qingyang Feng; Shaomeng Yu; Qianfeng Liu; Yang Cao; Guangzhao Tian; Yunfu Chen; Wei Qiu (European Journal of Agronomy, 2026)

Enhanced uranium (VI) removal in aqueous solutions via synergistic adsorption-reduction by phytic acid-modified MXene supported nZVI - Huaichang Yu; Mengqi Ma; Sisi Chu; Juanjuan Jiang; Linshan Fang; Tingting Sheng; Xiaoyu Li; Chuhan Qiu; Baowei Hu; Sen Yang (Chemical Engineering Journal, 2026)

Soil Erosion and Deposition Regulate Microbial Necromass Carbon Contributions to Soil Organic Carbon and Its Stability - Wentao Qiu; Lie Xiao; Zhanbin Li; Xuxu Min; Peng Li; Jianye Ma; Xiao Yang; Shu Yu; Tong Chou (Plant and Soil, 2026)

The relationships between the main root morphological characteristics and biomass allocation of Ageratina adenophora along the Qionghai lakeside, western Sichuan Plateau, China - Qun Li; Yu-Mei Qiu; Lan Chen; Cheng-Zhang Zhao; Bo Li; Hong Yang (Plant and Soil, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Unlocking microbial synergy in microalgae-bacteria granules: RSM-driven optimization and lifecycle microbial metagenomics for high-ammonia wastewater treatment - Yanni Geng; Chun-Ang Lian; Liming Yang; Spyros G. Pavlostathis; Xuejiao Qiao; Zhiguang Qiu; Yu Wang; Nan Dong; Anjie Li; Xubiao Luo; Ke Yu (Water Research, 2026)

Temperature-driven microbial dynamics and functional shifts in a pilot-scale partial nitrification/anammox reactor treating low-ammonium rare earth tailwater - Yu Zhang; Zhenyu Wang; Jiayi Li; Yongxing Chen; Junfeng Yang; Yonggan Li; Jiafu Qin; Heng Zhang; Guanglei Qiu; Xiaojun Wang (Journal of Environmental Chemical Engineering, 2026)

Chemical weathering releases substantial CO2 in temperate glacial catchments of the southeastern Tibetan Plateau - Zhengliang Yu; Guangjian Wu; Wei Yang; Lun Luo; Fei Li; Deji; Haiying Qiu; Yifan Pan; Xiong Xiao (Geochimica et Cosmochimica Acta, 2026)

Bisphenol exposure during pregnancy and serum total bile acid levels across trimesters: single and combined effects in pregnant women from Guangxi Zhuang, China - Jun Liang; Yu Zou; Zican Mo; Lixiang Pang; Kaiqi Yang; Peng Tang; Qian Liao; Liujuan Ou; Junshang Wen; Wanhui Li; Huishen Huang; Xiaoqiang Qiu (Environmental Pollution, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Integration of Multi-Omics and Machine Learning Identifies TGFB1 and SERPINE1 as Biomarkers of Vascular Smooth Muscle Cell Senescence in Intracranial Aneurysms - Haoran Qiu; Kai Chen; Yunruo Chen; Yang Yu; Xinlong Ma; Zhaoyang Yuan; Maogui Li; Jianfeng Zhuang; Mingxiang Zhang; Wandong Su; Yunyan Wang; Donghai Wang; et al. (Translational Stroke Research, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Impacts of cold spells on mortality risk in low-latitude subtropical plateau regions: a multi-dimensional analysis of spatial heterogeneity and vulnerability in Yunnan Province, China - Le-Yun Tan; Xian Tang; Yu-Hui Chen; Yang Chen; Qiu-Li Yu; Yuan-Yi Zha; Pi Guo; Qing-Ying Zhang (International Journal of Biometeorology, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

Growth phase-linked Sargassum-associated DOM structures microbial succession and carbon-nutrient coupling in a benthic Sargassum bed - Xiao-Li Ou; Long-Long Huang; Qiu-Jie Wang; Li-Li Xu; Lin-Jian Ou; Yu-Feng Yang (Marine Environmental Research, 2026)

Cobalt and Ruthenium Co-doping Activated Molybdenum Disulfide for Alkaline Electrocatalysis Oxygen Evolution Reaction - Yiwei Jiang; Yu Qiu; Xiaoting Zhang; Jiangbo Cao; Yuwei Zhang; Yu Wang; Zhenfeng Yang; Xueli Li; Yantu Zhang (Fuel, 2026)

224Ra labeled nanohydroxyapatite for targeted alpha therapy of metastatic lung cancer - Jie Lyu; Long Qiu; Fuyuan Tan; Yuying Yu; Xisheng Fan; Tianzhen Ye; Shuran Lei; Jiali Liao; Yuanyou Yang; Ning Liu; Feize Li (Chemical Engineering Journal, 2026)

Deciphering the role and mechanism of biochar dosage and inoculum-to-substrate ratio in modulating interspecies electron transfer and alleviating acid inhibition - Yu-Hong Qiu; Zi-Fan Wu; Jia-Bing Li; Zhi-Man Yang (Biomass and Bioenergy, 2026)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Polyimine vitrimers as recyclable and rehealable matrices for solid-state luminescent carbon dots - Xiaoran Yang; Fanhao Zeng; Yu Duan; Ruiyang Li; Ziyuan Liu; Yuanke Xiang; Shuangbin Liu; Zhili Peng; Li Qiu (Chemical Engineering Journal, 2025)

Ethylene oxide side chains and rhodanine end-groups incorporated in a star-shaped cathode interface molecule for high-performance organic solar cells - Zhi-Yong Qiu; Meng-Ting Wang; Peng Liu; Yu-Long Peng; Zaifang Li; Fang Yang; Lijian Zuo; Shi-Yong Liu (Chemical Engineering Journal, 2025)

Hydrogen bonding enforced supramolecular multifunctional nanocoating for implant osseointegration - Junhong Qiu; Qianqian Qiu; Jiawei Yang; Weilong Tang; Jiarong Xu; Yujie Chen; Hao Cai; Yuqi Wan; Zhilin Yu; Conrado Aparicio; Zhihua Li; Zhou Ye; et al. (Chemical Engineering Journal, 2025)

Amino-directed shifting ethylene/acetylene/ethane separation in pore-space-partitioned metal-organic frameworks - Li-Qiu Yang; Yan-Fei Li; Jia-Yao Liu; Ying Wang; Wen-Yu Yuan; Quan-Guo Zhai (Chemical Engineering Journal, 2025)

G Proteins-Associated Dose-Dependent Effects of Oxytocin on Oxytocin Neuronal Activity and Astrocytic Plasticity of the Supraoptic Nucleus - Xiao-Yu Liu; Shuo Ling; Yang Liu; Yunhao Jiang; Xiaoran Wang; Shuwei Jia; Chunmei Hou; Yanpeng Li; Delai Qiu; Yu-Feng Wang (Molecular Neurobiology, 2025)

A novel cucurbit[8]uril-based fluorescent probe for the detection of phenethylamine in urine - Min Chen; Wen Min; Shang-Wei Yuan; Carl Redshaw; Li-Xia Chen; Qiu-Yu Peng; Tao Yang; Zhu Tao; Xin Xiao (Analytica Chimica Acta, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

First demonstration of spaceborne L-band bistatic single-polarization single-baseline SAR interferometry on the retrieval of forest vertical structural information - Yang Lei; Weiliang Li; Yanghai Yu; Xiaotong Liu; Jie Xu; Anmin Fu; Jie Wan; Changcheng Wang; Wenli Huang; Zixuan Qiu; Tao Li; Haiqiang Fu; et al. (Remote Sensing of Environment, 2025)

Accumulation and translocation of antibiotic resistance genes in plants cultivated in hydroponic systems with nitrified biogas slurry - Huamei Chen; Jicai Yi; Yafei Li; Xinting Li; Hongli Zhang; Xince Yang; Haitao Zhong; Guangwei Yu; Rongliang Qiu; Yunxiao Chong (Journal of Hazardous Materials, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Ultrasound-triggered injectable piezoelectric nanocomposite hyaluronic acid-based hydrogel for modulating inflammation and chondrogenesis in osteoarthritis treatment - Juntao Lin; Shaobing Li; Yimeng Peng; Chongyin Qiu; Mingzhao Yang; Jiayi Guo; Bo Yu; Yan Chen (Carbohydrate Polymers, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Albumin mediates the association between maternal exposure to multiple metals and gestational diabetes mellitus: Findings from the Guangxi Birth Cohort Study - Hualong Qiu; Yu Bao; Shengzhu Huang; Yuen Zhong; Caitong He; Long Tian; Yu Zhang; Bangzhu Luo; Tao Liang; Baohong Pang; Mujun Li; Hong Cheng; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Tailoring hydrogen storage properties in cold rolled MgNiSi alloys: Microstructural evolution and low-temperature performance optimization - Shixin Sun; Junqi Qiu; Ziyi Guo; Haiyi Wan; Yuting Li; Hao Yang; Qing Peng; Yu'an Chen (Chemical Engineering Journal, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Heavy-metal-resistant characterization of Salinimicrobium maris sp. nov. potential significance in algal-bacterial interactions with Phaeocystis globosa - Fei Li; Lian Yu; Mingben Xu; Zhe Li; Caibi Lan; Qiu-Xia Yang; Jun-Xiang Lai (Algal Research, 2025)

Land surface temperatures outperform gridded air temperatures in modeling forest growth across the Northern Hemisphere - Feiyu Yang; Yujiu Xiong; Wenjin Wang; Hongxing Hu; Mantik Lai; Chao Zhang; Jiahao Cao; Leyao Zhu; Qibo Fan; Ying Zhao; Zhou Wang; Yaling Zhang; et al. (Agricultural and Forest Meteorology, 2025)

Nitrite impairs bioreactor performance due to decreased replication of Candidatus Brocadia sapporoensis by unbalanced energy allocation - Xuejiao Qiao; Liyu Zhang; Zhiguang Qiu; Yang Wu; Chunfang Deng; Yanni Geng; Yichi Zhang; Yan Yan; Bing Li; Lijuan Zhang; Wei-Qin Zhuang; Ke Yu (Water Research, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

“Framework Channel catalysis”: A multiphase synergistic Zn-based coating strategy for high-performance zinc-ion batteries - Yue Shi; Le Li; Chao Tan; Conghui Wang; Yuanyuan Yang; Haoyuan Du; Mengyao Guo; Xiaohu Yu; Zhigui Ren; Yongqiang Ji; Guotai Sun; Hengwei Qiu; et al. (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Whole genome sequencing reveals the lignocellulose-degrading potential of Calditerricola sp. DKC0303 in straw: From genomic insights to experimental confirmation - Zhongxu Duan; Xiangfen Kong; Guankai Qiu; Zhichao Kang; Shaoqing Zhang; Quanying Wang; Tianye Wang; Xiutao Yang; Nannan Li; Xuerong Han; Guopeng Zhu; Hongwen Yu (Journal of Cleaner Production, 2025)

Meroterpenoids with bicyclic polyprenylated acylphloroglucinol scaffold and anti-inflammatory activity from Hypericum lancasteri - Jin-Qiu You; Yun-Qi Jin; Yu-Meng Miao; Xin-Yu Sun; Jia-Yu Yang; Jin-Chang Huang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Trace element and sulfur isotope study of sulfide chimneys from the mafic-hosted Daxi Vent Field: Implications on the genesis of seafloor massive sulfide deposit at a segment end - Yejian Wang; Ming Yang; Xiqiu Han; Sven Petersen; Yiyang Cai; Xinkai Hu; Anxia Chen; Zhongyan Qiu; Xing Yu; Hang Hu; Matthias Frische; Honglin Li (Chemical Geology, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Identification and functional characterization of grass carp TRPV1 in facilitating GCRV infection - Zi-Yu Xie; Yang Xu; Qiu-Shi Zhang; Zhi-Ming Liu; Liang Hu; Wei Wang; Tiao-Yi Xiao; De-Liang Li; Xin-Yu Liang; Jun-Hua Li (Aquaculture, 2025)

PFOS causes lysosomes-regulated mitochondrial fission through TRPML1-VDAC1 and oligomerization of MCU/ATP5J2 - Wei Yang; Yu Li; Ruzhen Feng; Peiyao Liang; Kefan Tian; Lingli Hu; Kejing Wang; Tianming Qiu; Jingyuan Zhang; Xiance Sun; Xiaofeng Yao (Journal of Hazardous Materials, 2025)

Inhibitory activity of Moringa oleifera seed oil nanoemulsion against Staphylococcus aureus and its application in chicken meat preservation - Shuyun Ma; Lingfei Li; Ju Qu; Yu Yang; Qiu Yang; Yang Tian (Food Bioscience, 2025)

Boosting selectivity in glucose hydrogenation to sorbitol by optimizing Fe distribution in alloys and supports - Yixin Luo; Jingnan Yang; Fu Li; Xiaomei Zhou; Tongyan Yu; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Mendelian randomization and multi-omics analysis identify C4A as a critical protective biomolecule in head and neck squamous cell carcinoma - Ziqing Yang; Xinhui Qiu; Anquan Ma; Chenyang Wu; Xiaoyang Zong; Yifei Nie; Simin Zhan; Haoran Yang; Chengyuan Zhang; Huilu Song; Xu Wang; Zhihong Zhang; et al. (Chemical Engineering Journal, 2025)

Gold mineralization in the hydrothermal field at the termination of a detachment fault: A case study of the Tianxiu Vent Field - Ming Yang; Yejian Wang; Sven Petersen; Zhongyan Qiu; Honglin Li; Peng Zhou; Yiyang Cai; Xing Yu; Matthias Frische; Jiqiang Liu; Xiqiu Han (Mineralium Deposita, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Perfluorooctane sulfonate induced ferritinophagy via detyrosinated alpha tubulin-TRIM21-HERC2-regulated NCOA4 degradation in hepatocytes - Ruzhen Feng; Lingli Hu; Wei Yang; Peiyao Liang; Yu Li; Kefan Tian; Kejing Wang; Tianming Qiu; Jingyuan Zhang; Xiance Sun; Xiaofeng Yao (Environmental Pollution, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Construction of ultra-light and flexible aerogels with superior high oil sorption capacity by controlling the mechanical property of SiO2 nanofibers - Meng-Jie Chang; Ge Bai; Jun Liu; Xin Li; Hui Wang; Shu-Yi Hu; Qiu-Yu Hu; Shi-Shun Cao; Jie Yang (Journal of Environmental Chemical Engineering, 2025)

Compositional complexity of heterogeneous impact glasses in lunar soils: significance and pitfalls - Qian W. L. Zhang; Bin Su; Pierre Lanari; Jia-Hui Liu; Jia-Long Hao; Yu Liu; Liu-Yang Chen; Di Zhang; Jiang-Yan Yuan; Juan Wang; Xian-Hua Li; Qiu-Li Li (Contributions to Mineralogy and Petrology, 2025)
Heterogeneous impact glass beads are abundant in lunar soils and have been extensively used to study the geological processes that shaped the Moon’s surface. In this study, we examine the compositional complexity of three heterogeneous glass beads containing undigested zirconolite and zircon, using EPMA, Nano-SIMS mapping, and SIMS U–Pb isotope analyses. The undigested zircon and zirconolite crystals document three key volcanic events in the lunar history: at ~ 4.31 Ga the formation of alkali-suite rocks from the highlands, and at ~ 3.92 Ga, and ~ 2.04 Ga mare basalts, indicating that the U–Pb system in these zirconium-bearing crystals remains undisturbed during the ultra-high-temperature, short-duration impact melting events. EPMA and Nano-SIMS mapping reveal significant compositional inhomogeneity in the glass matrices, which complicates accurate provenance determination based on in-situ analysis. Bulk composition calculated from quantitative maps, however, provides a more reliable reference for inferring the origins of these beads. The high proportions of common Pb in the heterogeneous glass matrices, originating from diffusion-controlled processes during partial melting of impact involved minerals, introduce substantial uncertainties in U–Pb dating, complicating the interpretation of impact event ages. These findings highlight the challenges of U–Pb dating in heterogeneous glass beads and provide new insights into the preservation of pristine age information in lunar impact materials.

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Sustainable, biodegradable and flexible laminated passive cooling membrane for personal thermal and moisture comfort under direct sunlight - Qian Zhao; Yu Yang; Xuejie Yue; Tao Zhang; Yuqi Li; Dongya Yang; Fengxian Qiu (Chemical Engineering Journal, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Deterministic quantum state and gate teleportation between distant superconducting chips - Jiawei Qiu; Yang Liu; Ling Hu; Yukai Wu; Jingjing Niu; Libo Zhang; Wenhui Huang; Yuanzhen Chen; Jian Li; Song Liu; Youpeng Zhong; Luming Duan; et al. (Science Bulletin, 2025)

Molecular mechanism of pyrazosulfuron-ethyl degradation by Chenggangzhangalella sp. BI-1 and study on enhanced bioremediation of contaminated soil with rhammelolipid - Hao Zhang; Zi-wei Hua; Zi-yue Ding; Hui-ying Yang; Tie-jun Wang; Yu-ying Li; B. Larry Li; Xing Huang; Peng-fei Duan; Qiu-hong Niu (Journal of Environmental Chemical Engineering, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

Coupled vibratory roller and layered unsaturated subgrade model for intelligent compaction - Chuxuan Tang; Zheng Lu; Lang Qin; Tingzhou Yan; Jian Li; Yang Zhao; Yu Qiu (Computers and Geotechnics, 2025)

Nano titanium dioxide induces HaCaT cell pyroptosis via regulating the NLRP3/caspase-1/GSDMD pathway - Wanting Fu; Mingxue Liu; Yu Wang; Huimin Yang; Aoqi Ye; Jianhong Wu; Yang Li; Zejun Yu; Yinsheng Qiu; Lingyun Xu (Toxicology Letters, 2024)

ACSL4-mediated ZIP7-VDAC3 interaction regulates endoplasmic reticulum-mitochondria iron transfer in hepatocytes under PFOS exposure - Peiyao Liang; Kefan Tian; Wei Yang; Ruzhen Feng; Yu Li; Lingli Hu; Kejing Wang; Tianming Qiu; Jingyuan Zhang; Xiance Sun; Xiaofeng Yao (Science of The Total Environment, 2024)

In-situ and ex-situ selective catalysis of biochar-based catalysts for the production of high-quality bio-oil and H2-rich gas from tobacco stem - Xin Tang; Xiang Yang Li; Qiu Fa He; Yao Peng; Bin Peng; Yu Zhang; Wei Luo; Zhi Zhou (Journal of Environmental Chemical Engineering, 2024)

Effect of combined treatments of hydrolysis and succinylation on the solubility and emulsion stability of rennet casein and micellar casein - Hongjuan Li; Chuan Ren; Dongyu Hou; Xiaobao Qiu; Juan Zhang; Xiaohong Chen; Yang Zou; Guilian Sun; Kewen Li; Hongbo Li; Jinghua Yu (Food and Bioproducts Processing, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

A composite enzyme derived from papain and chymotrypsin reduces the Allergenicity of Cow's Milk allergen casein by targeting T and B cell epitopes - Ziyi Xiong; Jianfeng Cheng; Yongxin Hu; Siyi Chen; Yu Qiu; Anshu Yang; Zhihua Wu; Xin Li; Hongbing Chen (Food Chemistry, 2024)

Eutrophication driven macrophyte-derived organic matter decomposition to methane emission relates to co-metabolism effect in freshwater sediments - Xiaoguang Xu; Qiu Jin; Huazu Liu; Jie Ma; Yu Peng; Yuxuan Yang; Yang Deng; Chuanqiao Zhou; Wei Li; Xiaojun Zuo; Yiwen Zhou; Guoxiang Wang (Environmental Research, 2024)

Unveiling preferred chemoattractants for rhizosphere PGPR colonization by molecular docking and molecular dynamics simulations - Ran Chai; Fuxin Li; Yuqian Gao; Dehai Liu; Di Shang; Yanqing Yang; Jiayang Yu; Chenxiao Zhou; Yanan Li; Andong Song; Liyou Qiu (Computers and Electronics in Agriculture, 2024)

Imbalance of mitochondrial quality control regulated by STING and PINK1 affects cyfluthrin-induced neuroinflammation - Ji Zhao; Yi-kai Qiu; Yong-xing Xie; Xiao-yu Li; Yu-bin Li; Bing Wu; Yu-wen Wang; Xue-yan Tian; Yan-ling Lv; Ling-he Zhang; Wen-li Li; Hui-fang Yang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Two ethylene-responsive transcription factors, AdVAL2 and AdKAN2, regulate early steps in kiwifruit starch degradation - Yang Tong; Wen-yue Su; Yu-tong Chen; Xiao-fen Liu; Qiu-yun Zhang; Tong-hui Qi; Andrew C. Allan; Xiang Li; Xue-ren Yin (Postharvest Biology and Technology, 2024)

Soil and stone terraces offset the negative impacts of sloping cultivation on soil microbial diversity and functioning by protecting soil carbon - Yingbo Qiu; Qi Fu; Yihang Yang; Jiayi Zhao; Jiaxin Li; Fan Yi; Xianheng Fu; Yu Huang; Zhengchao Tian; Joshua L. Heitman; Zhiyuan Yao; Zhongmin Dai; et al. (Journal of Environmental Management, 2024)

Correction to: Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Transcriptome Sequencing and Mass Spectrometry Reveal Genes Involved in the Non-mendelian Inheritance-Mediated Feather Growth Rate in Chicken - Mohan Qiu; Zengrong Zhang; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Chenming Hu; Li Yang; Xiaoyan Song; Bo Xia; Chunlin Yu; et al. (Biochemical Genetics, 2024)
The feather growth rate in chickens included early and late feathering. We attempted to characterize the genes and pathways associated with the feather growth rate in chickens that are not in agreement with Mendelian inheritance. Gene expression profiles in the hair follicle tissues of late-feathering cocks (LC), early-feathering cocks (EC), late-feathering hens (LH), and early-feathering hens (EH) were acquired using RNA sequencing (RNA-seq), mass spectrometry (MS), and quantitative reverse transcription PCR (qRT‑PCR). A total of 188 differentially expressed genes (DEGs) were ascertained in EC vs. LC and 538 DEGs were identified in EH vs. LH. We observed that 14 up-regulated genes and 9 down-regulated genes were screened both in EC vs. LC and EH vs. LH. MS revealed that 41 and 138 differentially expressed proteins (DEPs) were screened out in EC vs. LC and EH vs. LH, respectively. Moreover, these DEGs and DEPs were enriched in multiple feather-related pathways, including JAK-STAT, MAPK, WNT, TGF-β, and calcium signaling pathways. qRT-PCR assay showed that the expression of WNT8A was decreased in LC compared with EC, while ALK and GRM4 expression were significantly up-regulated in EH relative to LH. This study helps to elucidate the potential mechanism of the feather growth rate in chickens that do not conform to genetic law.

Construction of an anti-anionic-depletion layer to mitigate the tip deposition effect for dendrite-free zinc anode - Xiaohui Li; Dan Qiu; Qiancheng Zhou; Ze Yang; Xing Zhou; Wenping Wang; Chenchen Wei; Ting Zou; Ying Yu (Chemical Engineering Journal, 2024)

Adaptive tetralactam macrocycle based polymers for efficient and rapid removal of organic micropollutants with wide scope - Yu Qiu; Shan Yu; Song-Meng Wang; Mei-Ling Liu; Shi-Yao Li; Huan Yao; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2024)

The protective effects of Kefir extract (KE) on intestinal damage in larval zebrafish induced by Oxytetracycline: Insights into intestinal function, morphology, and molecular mechanisms - Yang Qiu; Fujie Yan; Huilin Yu; Honghao Li; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Research International, 2024)

Enhancement of efficient molecular biology tools for Tremella fuciformis spore - Caiyuan Yu; Yuanwei Sun; Chunkai Yang; Yan Fang; Qi Meng; Yibin Qiu; Peng Lei; Hong Xu; Qi Zhang; Sha Li (Food Bioscience, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Interfacial Si–O–Zr bonds induced well dispersed zirconia on magnetic mesoporous silicas for enhanced tetracycline removal - Li-Jia Xie; Ying Tan; Yu-Qiu Ke; Kang-Qiang Lu; Kai Yang; Dan Li; Wei-Ya Huang; Yong-Cai Zhang; Zhao-Qing Liu (Chemical Engineering Journal, 2024)

Inhibition of pyrite oxidation through forming biogenic K-jarosite coatings to prevent acid mine drainage production - Maoxin Hong; Jun Wang; Baojun Yang; Yang Liu; Xin Sun; Laishun Li; Shichao Yu; Shitong Liu; Yang Kang; Wei Wang; Guanzhou Qiu (Water Research, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Monotonic trends of soil microbiomes, metagenomic and metabolomic functioning across ecosystems along water gradients in the Altai region, northwestern China - Qi Fu; Yingbo Qiu; Jiayi Zhao; Jiaxin Li; Siqi Xie; Qiuchang Liao; Xianheng Fu; Yu Huang; Zhiyuan Yao; Zhongmin Dai; Yunpeng Qiu; Yuchun Yang; et al. (Science of The Total Environment, 2024)

Kinetic studies of the secondary hydrate formation in porous media based on experiments in a cubic hydrate simulator and a new kinetic model - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yi-Song Yu; Qiu-Nan Lv; Yang Yu; Yi-Fan Weng; Jian-Wu Liu; Jian-Xing Yu (Fuel, 2024)

Liquid metal based conductive textile via reactive wetting for stretchable electromagnetic shielding and electro-thermal conversion applications - Lijuan Qiu; Jiazhuo Li; Qinglong Yu; Wanlin Han; Lijuan Zhao; Longfei Yi; Mingtao Yang (Chemical Engineering Journal, 2024)

Improving soil pH, nutrient concentrations, and enzyme activities by green manure returning in young and mature rubber plantation on Hainan Island, China - Wenxian Xu; Qiu Yang; Yamin Jiang; Jianan Yu; Jiale Li; Wenjie Liu; Zhixiang Wu (Plant and Soil, 2024)

Genome-wide identification of GATA transcription factor family and the effect of different light quality on the accumulation of terpenoid indole alkaloids in Uncaria rhynchophylla - Yingying Shao; Yu Zhou; Li Yang; Detian Mu; Iain W. Wilson; Yao Zhang; Lina Zhu; Xinghui Liu; Ling Luo; Jialong He; Deyou Qiu; Qi Tang (Plant Molecular Biology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

The association between blood heavy metals and gallstones: A cross-sectional study - Jia Wang; Yu-xin Sun; Shuai Xiang; Chen Yang; Xiang-jun Li; Meng-qi Zhang; Yu-jing Li; Xiao-xuan Li; Zhen-kang Qiu (Science of The Total Environment, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The alkaloids with neuroprotective effect from the root bark of Ailanthus altissima - Qing Shao; Tian-Yi Li; Wei Quan; Hui Wang; Ke-Yu Yan; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu (Natural Product Research, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

An in-field assembled hierarchical mesoporous electroenzymatic sensor for sensitive and real-time monitoring of nitrite - Xiao-Ying Qiu; Yuan-Yuan Cheng; Qiao Li; Yang-Yang Yu; Xiang Xiao (Journal of Cleaner Production, 2023)

Laser boosting the influx of calcium ions to enhance gasdermin e-dependent pyroptosis driven by a dual-layer polydopamine nanoagonist - Xiaoling Qiu; Weixi Jiang; Xun Guo; Chier Du; Xiaoting Wang; Yu Tian; Hongjin An; Jingxue Wang; Yuanli Luo; Yuan Guo; Peng Luo; Hua Teng; et al. (Chemical Engineering Journal, 2023)

Ultrarobust self-healing elastomers with hydrogen bonding connected MXene network for actuator applications - Chuansong Yu; Yuyan Wang; Xiaoyan Qiu; Jize Liu; Xinkai Li; Xin Yang; Xin Huang; Xinxing Zhang; Zhenming Chen (Chemical Engineering Journal, 2023)

Thermal and electrical conductive 2D CuO evaporator for all-day steam generation - Ze-Yu Yang; Lu-Qi Liu; Shan-Qiu Liu; Gang Wang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Improved prediction of rice yield at field and county levels by synergistic use of SAR, optical and meteorological data - Weiguo Yu; Gaoxiang Yang; Dong Li; Hengbiao Zheng; Xia Yao; Yan Zhu; Weixing Cao; Lin Qiu; Tao Cheng (Agricultural and Forest Meteorology, 2023)

A review of anaerobic granulation under high-salinity conditions: Mechanisms, influencing factors and enhancement strategies - Chen-Shun Lu; Jin-Ming Qiu; Yang Yang; Yong Hu; Yu-You Li; Takuro Kobayashi; Yong-Jun Zhang (Journal of Water Process Engineering, 2023)

The youngest lunar zircon reveals an extremely fractionated nature of Chang’e-5 basalt - Qin Zhou; Yu Liu; Saihong Yang; Qiu-Li Li; Yi Chen; Guangliang Zhang; Hongbo Zhang; Bin Liu; Dawei Liu; Jianjun Liu; Fu-Yuan Wu; Xian-Hua Li; et al. (Geochimica et Cosmochimica Acta, 2023)

Soil development following glacier retreat shapes metagenomic and metabolomic functioning associated with asynchronous C and N accumulation - Yu Huang; Wei Shi; Qi Fu; Yingbo Qiu; Jiayi Zhao; Jiaxin Li; Qian Lyu; Xian Yang; Jia Xiong; Wenzhi Wang; Ruiying Chang; Zhiyuan Yao; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Numerical simulation research of the transportation and distribution characteristics on sea surface of the microplastic released continuously for 12 years from China's coastal cities - Yan Li; Han Yu; Ying-hao Qin; Kai-xuan Guo; Yi-qiu Yang; Miao-yin Zhang; Wei Lu; Yu Zhang (Marine Environmental Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Fabrication and characterizations of Zn-doped SnO2-Ti4O7 anode for electrochemical degradation of hexafluoropropylene oxide dimer acid and its homologues - Zehong Yang; Qiongfang Zhuo; Wenlong Wang; Shuting Guo; Jianfeng Chen; Yanliang Li; Sihao Lv; Gang Yu; Yongfu Qiu (Journal of Hazardous Materials, 2023)

Evolution effect of -CF2- group amount in hydrofluoroether on the solvation structure and high voltage cycle performance of Ether-based localized High-concentration electrolytes - Pan Luo; Jun Yang; Ying Zhang; Li Liao; Qiu Chen; Bo Yu; Bingshu Guo; Mingshan Wang; Junchen Chen; Zhiyuan Ma; Yun Huang; Jiangtao Liu; et al. (Chemical Engineering Journal, 2023)

Third trimester as the susceptibility window for maternal PM2.5 exposure and preterm birth: A nationwide surveillance-based association study in China - Zhimei Qiu; Wenyan Li; Yang Qiu; Zhiyu Chen; Fumo Yang; Wenli Xu; Yuyang Gao; Zhen Liu; Qi Li; Min Jiang; Hanmin Liu; Yu Zhan; et al. (Science of The Total Environment, 2023)

Novel antiosteoporotic peptides purified from protein hydrolysates of taihe black-boned silky fowl: By larval zebrafish model and molecular docking - Yang Qiu; Jianyue Ying; Fujie Yan; Huilin Yu; Yan Zhao; Honghao Li; Shengyao Xia; Jianchu Chen; Jiajin Zhu (Food Research International, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Preparation of a novel metal-free polypyrrole-red phosphorus adsorbent for efficient removal of Cr(VI) from aqueous solution - Longyu Qiu; Yingjun Wang; Rui Sui; Chenxi Zhu; Weiwei Yang; Yongsheng Yu; Jiaming Li (Environmental Research, 2023)

Ionic liquid hybrid metal–organic frameworks for efficient adsorption and selective separation of ammonia at high temperature - Zhiyong Li; Yu Chen; Zhenzhen Wang; Yang Zhao; Qingchun Xia; Jikuan Qiu; Huiyong Wang; Jianji Wang (Chemical Engineering Journal, 2023)

Effect of E-beam irradiation on the qualitative attributes of shrimp (Penaeus vannamei) - Yan Zhao; Huilin Yu; Honghao Li; Yang Qiu; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Bioscience, 2023)

Application of macrocycle-crosslinked polymers as adsorbents for the removal of organic micropollutants from water - Shi-Yao Li; Dan Wang; Yu Qiu; Li-Li Wang; Liu-Pan Yang (Current Opinion in Green and Sustainable Chemistry, 2023)

Corrigendum to “High-level production of pullulan from high concentration of glucose by mutagenesis and adaptive laboratory evolution of Aureobasidium pullulans” [Carbohydr. Polym. 302 (2023) 120426] - Xiwen Li; Shuangzhi Zhao; Leilei Chen; Qingxin Zhou; Jiying Qiu; Xue Xin; Yanhao Zhang; Wei Yuan; Chengsen Tian; Xiaobin Yu; Jinyu Yang (Carbohydrate Polymers, 2023)

A framework for estimating all-weather fine resolution soil moisture from the integration of physics-based and machine learning-based algorithms - Pei Leng; Zhe Yang; Qiu-Yu Yan; Guo-Fei Shang; Xia Zhang; Xiao-Jing Han; Zhao-Liang Li (Computers and Electronics in Agriculture, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Key factors controlling the kinetics of secondary hydrate formation in the porous media - Chang-Wen Xiao; Xiao-Sen Li; Gang Li; Yang Yu; Yi-Fan Weng; Qiu-Nan Lv; Jian-Xing Yu (Gas Science and Engineering, 2023)

Non-concentrated electrolyte with weak anion coordination enables low Li-ion desolvation energy for low-temperature lithium batteries - Honglu Hu; Jinhan Li; Qiu Zhang; Guoyu Ding; Jiuding Liu; Yang Dong; Kang Zhao; Meng Yu; Huan Wang; Fangyi Cheng (Chemical Engineering Journal, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

High-level production of pullulan from high concentration of glucose by mutagenesis and adaptive laboratory evolution of Aureobasidium pullulans - Xiwen Li; Shuangzhi Zhao; Leilei Chen; Qingxin Zhou; Jiying Qiu; Xue Xin; Yanhao Zhang; Wei Yuan; Chengsen Tian; Jinyu Yang; Xiaobin Yu (Carbohydrate Polymers, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

The chemical characterization and source apportionment of PM2.5 and PM10 in a typical city of Northeast China - Deming Dong; Tao Qiu; Shanshan Du; Yu Gu; Anfeng Li; Xiuyi Hua; Yang Ning; Dapeng Liang (Urban Climate, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

The anti-TMV potency of the tobacco-derived fungus Aspergillus versicolor and its active alkaloids, as anti-TMV activity inhibitors - Jia-Meng Dai; Qi-Li Mi; Xue-Mei Li; Du Gang; Guang-Yu Yang; Jian-Duo Zhang; Jin Wang; Yin-Ke Li; Hai-Ying Yang; Dong Miao; Zhen-Jie Li; Qiu-Fen Hu (Phytochemistry, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Label-free therapeutic drug monitoring in human serum by the 3-step surface enhanced Raman spectroscopy and multivariate analysis - Yunpeng Wang; Cuiwei Yu; Haoyu Ji; Zhehan Liu; Xiaotong Wang; Yinghe Ji; Xiaomeng Sun; Yue Zhao; Xiaohong Qiu; Ting Zhang; Jing Li; Xin Liu; et al. (Chemical Engineering Journal, 2023)

RNA sequencing reveals lncRNA-mediated non-mendelian inheritance of feather growth change in chickens - Mohan Qiu; Chunlin Yu; Shiliang Zhu; Siyang Liu; Han Peng; Xia Xiong; Jialei Chen; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Chaowu Yang (Genes & Genomics, 2022)
Background Long non-coding RNAs (lncRNAs) play an essential role in biological processes. However, the expression patterns of lncRNAs that regulate the non-Mendelian inheritance feather phenotypes remain unknown. Objective This study aimed to compare the expression profiles of lncRNAs in the follicles of the late-feathering cocks (LC) and late-feathering hens (LH) that followed genetic rules and the early-feathering hen (EH) and early-feathering cock (EC) that did not conform to the genetic laws. Methods We performed RNA sequencing and investigated the differentially expressed lncRNAs (DElncRNAs) between the early- and late-feathering chickens, which function by cis-acting or participate in the competing endogenous RNA (ceRNA) network. Results A total of 53 upregulated and 43 downregulated lncRNAs were identified in EC vs. LC, and 58 upregulated and 109 downregulated lncRNAs were identified in EH vs. LH. The target mRNAs regulated by lncRNAs in cis were enriched in the pentose phosphate pathway, TGF-β signaling pathway and Jak-STAT signaling pathway in EC vs. LC and were associated with the TGF-β signaling pathway, Wnt signaling pathway, p53 signaling pathway and Jak-STAT signaling pathway in EH vs. LH. In addition, the lncRNA-mediated ceRNA regulatory pathways of hair follicle formation were mainly enriched in the TGF-β signaling pathway, Wnt signaling pathway, melanogenesis, and calcium signaling pathways. The levels of ENSGALG00000047626 were significantly higher in the late-feathering chickens than in the early-feathering chickens, which regulated the expression of SSTR2 by gga-miR-1649-5p. Conclusion This study provides a novel molecular mechanism of lncRNA’s response to the feather rate that does not conform to the genetic laws in chickens.

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

The Location Reliability of the Resting-State fMRI FC of Emotional Regions Towards rTMS Therapy - Na Zhao; Juan Yue; Zi-Jian Feng; Yang Qiao; Qiu Ge; Li-Xia Yuan; Jue Wang; Yu-Tao Xiang; Yu-Feng Zang (Neuroinformatics, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

XPS and NMR analyze the combined forms of Pb in Cladophora rupestris subcells and its detoxification - Qiu-yu Chen; Liu Yang; Lei Liu; Xuan-xuan Li; Hai-dong Li; Qian Zhang; De-ju Cao (Environmental Science and Pollution Research, 2022)

Triggering of rockburst in layered composite rocks - Jian-Zhi Zhang; Hao-Yu Qiu; Yang-Bing Cao; Bing-Lei Li (Arabian Journal of Geosciences, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Reducing methane emission by promoting its oxidation in rhizosphere through nitrogen-induced root growth in paddy fields - Siyu Li; Yun Chen; Feng Yu; Yajun Zhang; Kun Liu; Xinxin Zhuo; Yuanyuan Qiu; Hao Zhang; Junfei Gu; Weilu Wang; Jianchang Yang; Lijun Liu (Plant and Soil, 2022)

Quercetin Alleviates Demyelination Through Regulating Microglial Phenotype Transformation to Mitigate Neuropsychiatric Symptoms in Mice with Vascular Dementia - Zihu Tan; Guang Yang; Jing Qiu; Wenjing Yan; Yu Liu; Zhengling Ma; Jia Li; Jing Liu; Nan Shan (Molecular Neurobiology, 2022)

Microbial communities in swamps of four mangrove reserves driven by interactions between physicochemical properties and microbe in the North Beibu Gulf, China - Lu Li; Chunyan Peng; Zicong Yang; Yu He; Meng Liang; Hongmin Cao; Qinghua Qiu; Jingjing Song; Youlu Su; Bin Gong (Environmental Science and Pollution Research, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Correction to: AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

High-throughput sequencing revealed the expression profile and potential key molecules of the circular RNAs involved in the process of hypoxic adaptation in Tibetan chickens - Zengrong Zhang; Mohan Qiu; Huarui Du; Qingyun Li; Wu Gan; Xia Xiong; Chunlin Yu; Han Peng; Bo Xia; Xiaoyan Song; Li Yang; Chenming Hu; et al. (Biologia, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Long Non-coding RNA Expression Profile in Broiler Liver with Cadmium-Induced Oxidative Damage - Chunlin Yu; Chaowu Yang; Xiaoyan Song; Jingjing Li; Han Peng; Mohan Qiu; Li Yang; Huarui Du; Xiaosong Jiang; Yiping Liu (Biological Trace Element Research, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

AMPK-SIRT1-PGC1α Signal Pathway Influences the Cognitive Function of Aged Rats in Sevoflurane-Induced Anesthesia - Xiao-Yu Yang; Qiu-Jun Li; Wen-Chao Zhang; Shao-Qiang Zheng; Zhi-Jun Qu; Yang Xi; Geng Wang (Journal of Molecular Neuroscience, 2020)

Deformation and failure of a high-steep slope induced by multi-layer coal mining - Jian-le Yu; Jian-jun Zhao; Hao-yuan Yan; Qi-yi Lai; Run-qiu Huang; Xiu-wei Liu; Yang-chnn Li (Journal of Mountain Science, 2020)

Plasticity of the resting-state brain: static and dynamic functional connectivity change induced by divergent thinking training - Jiangzhou Sun; Qinglin Zhang; Yu Li; Jie Meng; Qunlin Chen; Wenjing Yang; Dongtao Wei; Jiang Qiu (Brain Imaging and Behavior, 2020)

Sea-level changes controlled detrital sediment inputs to the Bicol Shelf in the western Philippine Sea since 150 ka - Zhishun Zhang; Fuqing Jiang; Tiegang Li; Dezhou Yang; Xiaojing Zhou; Zhifang Xiong; Xiaohua Qiu; Qi Jia; Yu Yan; Xuguang Feng (Journal of Oceanology and Limnology, 2020)

Effects of free-range broiler production on vegetation characteristic and soil physicochemical property of the stocking areas in China - Chunlin Yu; Xiaosong Jiang; Huarui Du; Qingyun Li; Zengrong Zhang; Mohan Qiu; Tianbao Chen; Bo Xia; Xiaoyan Song; Chenming Hu; Xia Xiong; Li Yang; et al. (Agroforestry Systems, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

ACT001 modulates the NF-κB/MnSOD/ROS axis by targeting IKKβ to inhibit glioblastoma cell growth - Qiuying Li; Yu Sun; Bowen Liu; Jiabo Li; Xin Hao; Weizhi Ge; Xuemei Zhang; Shiqi Bao; Jianmiao Gong; Zhenhuan Jiang; Chuanjiang Qiu; Liqing Zhao; et al. (Journal of Molecular Medicine, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Complete plastid genome of Larix potaninii var. macrocarpa, an endangered conifer endemic to China - Dai-Yu Qiu; Jiao Yang; Li Feng; Ding-Wen Ni; Cai-Xia Huang; Zhong-Hu Li (Conservation Genetics Resources, 2018)

Complete genome sequence of shrimp hemocyte iridescent virus (SHIV) isolated from white leg shrimp, Litopenaeus vannamei - Liang Qiu; Meng-Meng Chen; Ruo-Yu Wang; Xiao-Yuan Wan; Chen Li; Qing-Li Zhang; Xuan Dong; Bing Yang; Jian-Hai Xiang; Jie Huang (Archives of Virology, 2018)

Involvement of NF-κB and the CX3CR1 Signaling Network in Mechanical Allodynia Induced by Tetanic Sciatic Stimulation - Zhe-Chen Wang; Li-Hong Li; Chao Bian; Liu Yang; Ning Lv; Yu-Qiu Zhang (Neuroscience Bulletin, 2018)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Association of Toll-like receptor 3 gene polymorphism with the severity of enterovirus 71 infection in Chinese children - Hongfang He; Shihai Liu; Pei-pei Liu; Qiu-bo Li; Yu-xia Tan; Ya Guo; Fei Li; Yuan-yuan Wang; Ye-dan Liu; Cheng-qing Yang; Zong-bo Chen (Archives of Virology, 2017)

Gap junction protein connexin43 deregulation contributes to bladder carcinogenesis via targeting MAPK pathway - Xiao-lin Ai; Qiang Chi; Yu Qiu; Hong-yang Li; Dong-jie Li; Jia-xu Wang; Zhi-yong Wang (Molecular and Cellular Biochemistry, 2017)

Monazite RW-1: a homogenous natural reference material for SIMS U–Pb and Th–Pb isotopic analysis - Xiao-Xiao Ling; Magdalena H. Huyskens; Qiu-Li Li; Qin-Zhu Yin; Ronald Werner; Yu Liu; Guo-Qiang Tang; Ya-Nan Yang; Xian-Hua Li (Mineralogy and Petrology, 2017)

Molecular characterization of Sp110 gene in pigs - Li-zu Li; Qiu-shi Wang; Li-xin Han; Jin-kui Wang; Si-yu Shao; Liang Wang; Di Liu; Xiu-qin Yang (Molecular Genetics and Genomics, 2016)

Opposite Sex Contact and Isolation: A Novel Depression/Anxiety Model - Liu Yang; Li-Jun Shi; Bei Tang; Qiu-Qin Han; Jin Yu; Gen-Cheng Wu; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Enhancement of Biocontrol Activities and Cyclic Lipopeptides Production by Chemical Mutagenesis of Bacillus subtilis XF-1, a Biocontrol Agent of Plasmodiophora brassicae and Fusarium solani - Xing-Yu Li; Jing-Jing Yang; Zi-Chao Mao; Hon-Hing Ho; Yi-Xing Wu; Yue-Qiu He (Indian Journal of Microbiology, 2014)

Downregulation of Neuregulin 1-ErbB4 Signaling in Parvalbumin Interneurons in the Rat Brain May Contribute to the Antidepressant Properties of Ketamine - Nan Wang; Guang-Fen Zhang; Xiao-Yu Liu; He-Liang Sun; Xing-Ming Wang; Li-Li Qiu; Chun Yang; Jian-Jun Yang (Journal of Molecular Neuroscience, 2014)

AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2014)

A novel NAC transcription factor from Suaeda liaotungensis K. enhanced transgenic Arabidopsis drought, salt, and cold stress tolerance - Xiao-lan Li; Xing Yang; Yu-xin Hu; Xiao-dong Yu; Qiu-li Li (Plant Cell Reports, 2014)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Synthesis, molecular modeling, and biological evaluation of 1,2,4-triazole derivatives containing pyridine as potential anti-tumor agents - Yan-Bin Zhang; Wen Liu; Yu-Shun Yang; Xiao-Liang Wang; Hai-Liang Zhu; Li-Fei Bai; Xiao-Yang Qiu (Medicinal Chemistry Research, 2013)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Improved methods for basic molecular manipulation of the red alga Porphyra umbilicalis (Rhodophyta: Bangiales) - Li-En Yang; Qiu-Ping Jin; Yu Xiao; Pu Xu; Shan Lu (Journal of Applied Phycology, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Expression and function of two chaperone proteins, AtGroEL and AtGroES, from Acidithiobacillus ferrooxidans ATCC 23270 - Wenqing Qin; Qiuxia Huang; Jianyu Zhu; Peng Yang; Runlan Yu; Jiaokun Li; Xueduan Liu; Guanzhou Qiu (World Journal of Microbiology and Biotechnology, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

The Pathway and Regulation of Salicylic Acid Biosynthesis in Probenazole-Treated Arabidopsis - Jin Yu; Jiong Gao; Xiao Yan Wang; Qiang Wei; Li Feng Yang; Kai Qiu; Ben Ke Kuai (Journal of Plant Biology, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Molecular identification and the complete nucleotide sequence of TYLCV isolate from Shanghai of China - Zhang Yongping; Zhu Weimin; Cui Huimei; Qiu Yang; Sha Kun; Wan Yanhui; Zhu Longying; Yu Li; Hui Zhang (Virus Genes, 2008)

Agrobacterium–mediated genetic transformation of Elymus breviaristatus with Pseudomonas pseudoalcaligenes insecticidal protein gene - Daxu Li; Qun Sun; Min Huang; Jie Zhang; Shiqie Bai; Linyong Zheng; Jian Zhao; Dunlian Qiu; Li Li; Zhirong Yang; Minghong You; Gang Liu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)